Bjerke_et_al_Nord_J_Bot_2018_Fig_5_leaf colour - Bjerke, Jarle; Wierzbinski, Grzegorz; Tømmervik, Hans; Phoenix, Gareth; Bokhorst, Stef (Dryad Digital Repository, 2018)
Temporal changes in frequency of leaf colour state during the 2016 growing season. nm = not measured.